The LIBER Workshops on the “Open Archives Initiative” at CERN, Geneva - Dekeyser, Raf (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2006)
In 2000 the Open Archives Initiative (OAI) was still in its early stages. It was often still called the Santa Fe Convention, which refers to a meeting in October 1999 of representatives from a number of institutions that maintained or planned e-print archives for open access, and from organizations interested in providing services on the data in those archives (such as search interfaces). This convention was an initiative of Paul Ginsparg, Rick Luce and Herbert Van de Sompel (all three working at that time at the Los Alamos National Laboratory) and it resulted in an agreement about a technical and organizational framework for achieving interoperability among e-print archives. The first European meeting on OAI took place in September 2000 in Lisbon, in conjunction with a meeting of the European Computer Driving Licence Foundation (ECDL), and therefore more oriented to computer specialists than to librarians.